Light and electron microscopy of globular hyaline inclusions in liver cells - Underwood, J. C. E. (1972)
Numerous large globular hyaline inclusions were found in the liver cells of a patient with congestive cardiac failure due to cor pulmonale. The nature of the inclusions is discussed with particular emphasis on certain ultrastructural features which suggest a possible derivation from peroxisomes.